Hollywood or history? : an inquiry-based strategy for using the Simpsons to teach social studies - Whitlock, Annie McMahon (Hollywood or history?, 2024)
"The FOX television show The Simpsons has been around for over 30 years, with more than 700 episodes. A satirical, animated comedy, The Simpsons has millions of fans around the world and its numerous characters are instantly recognizable. Two of the main characters, children Bart and Lisa, are in elementary school and their educational experience is satirized frequently, with episodes taking place at Springfield Elementary and featuring their teachers, classmates, and administration-often with biting criticism of curriculum, privatization, and standardized testing, to name a few. The Simpsons also features episodes retelling historical events, where the family experiences different countries and cultures, and participates in the political process. The Simpsons is unique in that the show itself is also a historical source, having been on the air since 1989. Issues that were current in the early 1990s at the height of popularity of The Simpsons are now considered historical, and there is room in classrooms to critically analyze the show with students about whether the show has adapted well to the 2020s, particularly with the show's use of cultural stereotypes. This edited book offers a collection of classroom-ready tools based on the Hollywood or History? strategy and designed to foster historical inquiry through the careful use of episodes or clips from The Simpsons. This book will be organized by the 10 Themes of Social Studies as outlined by the National Council for the Social Studies (NCSS, 2010). Each of these 10 sections of the book feature two or three lesson plans from the massive catalog of The Simpsons. There is also an 11th section featuring two lesson plans using episodes of The Simpsons that satirize public education more broadly, which can be used by teacher candidates in methods classrooms to examine the realities of the history of public education and current issues that affect the profession"--